Analisis Faktor-Faktor yang Berpengaruh Terhadap Alokasi Belanja Modal (Studi Empiris pada Pemerintah Kabupaten dan Kota di Jawa Timur Periode Tahun 2010-2014) - Kurniati, Putri Tri, Eny Kusumawati, SE, MM, Ak, CA (2017)
The aim of this research is to analyze the influence oflocally generated revenue (PAD), revenue sharing (DBH), special allocation fund (DAK), personnel expenditure, and remaining balance budget (SiLPA) on the capital expenditure in the local government and city district East Java in the period 2010-2014. The population of this research is budget realization report all of districts and cities in East Java in the period2010-2014. Research sampling used purposive sampling technique and found 11 districtsand 3 cities, with 5 years of observation. So, the total sample studied was 70. The collected data was analyzed using classic assumption test and then do hypothesis test. Testing the hypotesis in this study using multiple regression analysis with t-test, F, and the coefficient of determination. The results indicate thatlocally generated revenue and personnel expenditurehave a significant influence on the capital expenditure. Meanwhile, revenue sharing, special allocation fund, and remaining balance budgetdon't have significant influence on the capital expenditure.